2013
DOI: 10.1097/mat.0b013e318291fbaa
|View full text |Cite
|
Sign up to set email alerts
|

Blood Substitutes

Abstract: The development of oxygen (O2) carrying blood substitutes has evolved from the goal of replicating blood O2 transports properties to that of preserving microvascular and organ function, reducing the inherent or potential toxicity of the material used to carry O2, and treating pathologies initiated by anemia and hypoxia. Furthermore, the emphasis has shifted from blood replacement fluid to “O2 therapeutics” that restore tissue oxygenation to specific tissues regions. This review covers the different alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 229 publications
(279 reference statements)
0
35
0
Order By: Relevance
“…To overcome this problem, intensive research is being pursued to develop new carriers able to release therapeutically significant amounts of oxygen to tissues in an effective and time-sustained manner [ 12 , 13 ]. Hemoglobin (Hb)-based oxygen carriers have been developed as cell-free suspensions, either encapsulated within vehicles, or complexed with protective enzymes [ 12 , 13 ]. Alternative carriers are based on perfluorocarbons, which can carry molecular oxygen without actually binding it, thus favoring gas exchange [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, intensive research is being pursued to develop new carriers able to release therapeutically significant amounts of oxygen to tissues in an effective and time-sustained manner [ 12 , 13 ]. Hemoglobin (Hb)-based oxygen carriers have been developed as cell-free suspensions, either encapsulated within vehicles, or complexed with protective enzymes [ 12 , 13 ]. Alternative carriers are based on perfluorocarbons, which can carry molecular oxygen without actually binding it, thus favoring gas exchange [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alternative carriers are based on perfluorocarbons, which can carry molecular oxygen without actually binding it, thus favoring gas exchange [ 14 ]. However, they are not water-miscible, and therefore need to be formulated into emulsions for in vivo use [ 12 , 14 ]. Unfortunately, despite attractive characteristics, no perfluorocarbon-based oxygen emulsion is currently approved for clinical uses: some of them, such as Fluosol-DA, have failed due to secondary effects of the surfactants employed, whereas others, such as Oxygent, displayed adverse cerebrovascular effects on cardiopulmonary bypass [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the availability of blood is limited in emergency situations such as in war zones or after natural disasters (5). Therefore, the development of a therapeutic product that can suitably replace blood transfusion in cases of severe hemorrhage or during major cardiovascular surgery has been a goal of scientific and commercial efforts (6). Hemoglobin, the protein responsible for the transport of O 2 in the RBC, has served as the precursor for the formulation of blood substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…From the first generation of HBOCs, we learned that acellular Hb depletes endothelial nitric oxide (NO) via a NO dioxygenase reaction that produces vasoconstriction and hypertension (13, 14). Other negative reactions partially responsible for vasoconstriction and hypertension exerted by first generation HBOCs were the extravasation of acellular Hb due to its small molecular size, as well as metabolic regulation of blood flow in response to hyper-oxygenation due to facilitated O 2 transport by the acellular Hb (15, 16). To overcome these issues, different strategies have been developed, including Hb polymerization and Hb surface decoration with polyethylene glycol (PEG) (17).…”
Section: Introductionmentioning
confidence: 99%
“…PFC-in-water emulsions intended for biomedical use are produced at concentrations ranging from 20 % up to 120 % weight/volume. Osmolarity of the suspending media is independent of liquid PFC concentration and is adjusted by the addition of tonicity agents (Cabrales and Intaglietta, 2013). Up to date, several emulsion systems based on a few liquid PFC agents have been commercially developed and they are generally in preclinical/clinical trials, as reported in Table 3 plant-origin additives, α-tocopherol).…”
Section: Liquid Pfc-based Emulsionsmentioning
confidence: 99%